Comparative Study of Shear Bond Strength of Recycled Brackets using different Recycling Techniques – An in vitro study - Singh, Rajeshwar; Chaudhary, Varunjeet; Lahoti, Seema; Lahoti, Kapil (Orthodontic Journal of Nepal, 2016)
Introduction: The debonding of brackets is common in orthodontic practice. It may be due to bond failure or as a need for bracket repositioning. Typically practitioners shall discard dislodged brackets and replace it with a new bracket or reuse the bracket Objective: To compare and evaluate the shear bond strength of recycled orthodontic brackets using different methods. Materials & Method: A total of 50 extracted premolars and 50 metal brackets with a slot configuration of 0.022”x0.028” were used. All samples were divided into 5 groups with 10 samples each. Each group was further divided into 2 groups which were control group and experimental group. Experimental group was further subdivided into four recycle sub-groups. Tooth surface were prepared for bonding then brackets were bonded. The specimens were tested on Universal Testing Machine for shear bond strength. The force producing bond failure was recorded in Newtons (N) and converted into megapascals (Mpa). Result: Shear bond strength of control group was maximum among all recycled groups. Shear bond strength of recycled brackets bonded with silane coupling agent and recycled with flaming, electropolishing, sandblasting and ultrasonic cleaning was equivalent to the control group. Brackets recycled with flaming and sandblasting had less shear bond strength as compared to control group. Brackets recycled with flaming and electropolishing were having the least shear bond strength. Conclusion: Brackets recycled with flaming, ultra sonic scaling, electropolishing and treated with silane coupling agent was recorded with highest shear bond strength. Sandblasting of metal brackets to remove composite residue, had insignificant effect on the shear bond strength. Hence sandblasting should be considered as viable, time saving and convenient method of recycling.